Evaluation of Seedling Tray Selection for the Screening of Saline-Tolerant Rice - Muhammad Fuad Anshori*; Nur Qalbi Zaesar Muharram; Indrayani Muslim; A, Chamsitasari Zulfikarahmi A. Jamil; Muh. Fikri Al Qautzar (Universitas Sembilanbelas November Kolaka, 2023)
This study aimed to identify the effectiveness of seedling trays in screening rice for salinity tolerance. The study was conducted at the greenhouse, Faculty of Agriculture, Hasanuddin University, from August 2022 to October 2022. The genotypes used consisted of 4 dihaploid lines (F37, F42, F46, and F47), which were tolerant to salinities in nutrient culture screening. The Duncan Multiple Range Test (DMRT) with STAR 2.0.1 software and regression analysis with Microsoft Excel were used to analyze the interaction between genotype and environment. The results showed that the characters of shoot length (SL) and shoot fresh weight (SFW) were significantly influenced by all sources of diversity. In addition, the F37 and F42 genotype had a stable tolerance to saliency stress. The SFW character of F42 was more affected by SL than SL in the screening with soil media in trays. Based on the two evaluation characters (SL and SFW), fixed crown height is recommended as a selection criterion with SFW for the screening of saline-tolerant rice.